Expression and characterization of bifunctional fusion proteins possessing antitumor and thrombolytic function for targeting therapy. (27th May 2015) - Hui, Jing; Lin, Jia‐shuai; Hu, Ying; Li, Hui; Hu, Feng‐qing
Abstract: It is a usual clinical phenomenon that cancer patients are prone to thrombosis. Until now, there have been no efficient methods or appropriate drugs to prevent and cure tumor thrombus. ΔSEC2, N ‐terminal deletion of 17 amino acids and C ‐terminal deletion of 132 amino acids, retained antitumor activity of SEC2. ΔSak, N ‐terminal deletion of 10 amino acids, had thrombolytic activity and specificity advantages. By utilizing bioactivities of ΔSEC2 and ΔSak, ΔSEC2–ΔSak and ΔSak–ΔSEC2 were constructed. Octreotide is a tumor targeting peptide and it can be combined with somatostatin (SST) receptors of tumor surface in ligand–receptor binding way. It can be used to increase specificity for tumor therapy. Based on previous studies, DNA sequence encoding octreotide gene was inserted into plasmid pET‐28a –Δsec2–Δsak and pET‐28a –Δsak–Δsec2 . After expression and purification, fusion proteins could significantly stimulate proliferation of mouse spleen lymphocyte, obviously inhibit the growth of human gastric carcinoma BGC‐823, and have thrombolytic activity, indicating that fusion proteins retained bioactivities of staphylococcal enterotoxin C2 and Sak. Furthermore, tumor binding capacity of fusion protein was confirmed through the coimmunoprecipitation method. The result showed that they could bind SST receptor 2 antibody, indicating that fusion proteins could be specifically targeted to tumor surface. It has important significance and may be used for targeted therapy.